APPLE'S SILENT MARKETING STRATEGY ADAPTS TO LOCAL CULTURAL VALUES IN THE GLOBAL MARKET - Qamara, Syabina Al; Kusumawati, Rina; Zahro, Fatimatuz (Universitas Islam Malang, 2024)
In a dynamic global marketing landscape, Apple's silent marketing strategy offers an interesting alternative approach to conventional promotional practices. Rather than relying on explicit advertising and persuasive language, Apple communicates through symbolic design, minimalist aesthetics, and immersive customer experiences. This study aims to analyze how Apple's silent marketing strategy adapts to local cultural values across various global markets without compromising its global brand identity. Using a Systematic Literature Review (SLR) approach, this study synthesizes findings from 30 academic sources published between 2005 and 2024, covering markets such as the United States, Japan, and Indonesia. The results reveal three key findings: first, Apple consistently conveys its brand message through visual narratives and experiential design; second, Apple implements symbolic cultural adaptation by adjusting visual elements and spatial aesthetics to local norms; and third, consumer interpretation of silent communication is mediated by cultural context, particularly effective in high-context societies such as Japan and Indonesia. From a theoretical perspective, this study strengthens the relevance of cultural branding and cross-cultural communication theories in understanding how global brands operate. Practically, this study offers strategic implications for global marketers in balancing standardization with local sensitivity. Ultimately, silent marketing is not just a tactic, but a communication philosophy that constructs meaning through emotions, symbols, and cultural empathyto reduce the negative impacts of global trade tensions.